(3Jbjje eDTQGJ LhOI GdMjGI aj SjGSGJ efGWb GdEScGf ZjQ GdQSej aj eUQ (B/s - (3,g``fO j``S Ydi YK``eGfs; (3GMeO eMehO jSQjs; (3TjeGA YHO GdhgGH eMeO s (2024)
(3gPG GdHMK jbOe OQGSI ddYdGbI GdJaGYdjI Hjf GdeLJeY hGdHjFI GdMVQjI ef LgI, heaghe LhOI GdMjGI ef NdGd eDTQGJg GdQFjSjI GdJj jLH Cf Jchf eJhaQI aj GdeLJeY ef LgI CNQi, HGdEVGaI Edi JMdjd GdeYGjjQ hGdeDTQGJ GdeJYdbI HGdScGf hSdhc GdCaQGO aj gPG GdeLJeY, aVdkG Yf eOi QVG GdCaQGO Yf GdefWbI GdScfjI GdJj jYjThf ajgG(B. (3jJe Pdc ef NdGd OQGSI HYV GdJLGQH GdeMdjI hGdOhdjI GdJj JMdd eaghe LhOI GdMjGI(B. (3hbO CSaQJ GdOQGSI Yf GSJfJGL Cf eaghe LhOI GdMjGI dg fWGb hGSY, jTed GdYOjO ef GdeDTQGJ GdeNJdaI(B. (3hGdYGed GdQFjSj GdPj jcef hQGA YedjI GdJbjje gh GdHTQ, hCf gfGc JQGHkWG Hjf eaghe LhOI GdMjGI hGdSjGSGJ GdJj JJYGed eY efGWb GdEScGf ZjQ GdQSej, MjK Cf JMSjf SjGSGJ GdEScGf ZjQ GdQSej jYfj JMSjf LhOI GdMjGI(B. (3hCMO GdWQb gh OeL eTGQcI GdeLJeY aj JMSjf GdHjFI GdMVQjI deSGYOI GdCTNGU GdabQGA GdPjf dG jSJWjYhf JdHjI GMJjGLGJge aj GdScf(B. (3hjJVef GdHMK GSJfJGLGJ TGedI dLejY GdYfGUQ GdfXQjI GdeOQhSI HGdEVGaI Edi JMdjd GdYfGUQ GdeMOOI ddCWQ GdfXQjI, eaghe LhOI GdMjGI aj GdefGWb GdScfjI hSjGSGJ GdJYGed eY efGWb GdEScGf ZjQ GdQSej aj eUQ, hJchjf GdEWGQ GdfXQj GdfgGFj GdeOeL Hjf GdeLGdjf(B. (3ceG jTed fJGFL eMOOI ddJLGQH GdeMdjI aj efGWb eYjfI, hJMdjd Objb dfJGFL GdGSJHjGfGJ hebGHdGJ GdNHQGA, HGdEVGaI Edi JbOje JhUjGJ TGedI JYcS QDjI ddeTcdI GdHMKjI hJWQM GbJQGMGJ dOQGSGJ eSJbHdjI aj faS eLGd GdHMK(B.s
This research presents a study of the This research presents a study of the interactive relationship between society and the urban environment on the one hand, and the concept of quality of life through its main indicators that must be available in society on the other hand, in addition to an analysis of standards and indicators related to the population and the behavior of individuals in this community, as well as the extent of individuals$1 (Bsatisfaction with The residential area in which they live. This is done by studying some local and international experiences that analyze the concept of quality of life. The study resulted in the conclusion that the concept of quality of life has a broad scope, including many different indicators. The main factor behind the evaluation process is people, and there is an interconnection between the concept of quality of life and policies that deal with informal housing areas, as improving informal housing policies means improving the quality of life. One way is to incorporate community participation in improving the urban environment to help poor people who cannot meet their housing needs. The research includes comprehensive conclusions for all the theoretical elements studied in addition to an analysis of the specific elements of the theoretical frameworks, the concept of quality of life in residential areas and policies for dealing with informal housing areas in Egypt, and the formation of the final theoretical framework combined between the two fields. It also includes specific results of local experiences in specific regions, careful analysis of the results of questionnaires and expert interviews, in addition to providing comprehensive recommendations that reflect a vision of the research problem and put forward suggestions for future studies in the same field of research.s
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B134-147.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdGMjGA GdScfjIs; (3GdGScGfs -- (3GfhGYs; (3Jbjjes -- (3LhOI GdMjGIs -- (3LhOI GdMjGI GdYeQGfjIs -- (3efGWb GdEScGfs